Penerapan Lesson Studi Melalui Pelatihan Pola In-On-In dalam Meningkatkan Mutu Pembelajaran Pada Madrasah Ibtidaiyah - Durahman Durahman (Jurnal IAI Bunga Bangsa Cirebon, 2021)
Improving the quality of education can be started by improving the quality of teachers in teaching and professional behavior. Teacher upgrading and training is one form of the effort. The teacher coaching model to achieve the quality of learning in school is Lesson Study. Lesson Study is a